Analysis Of Acceptance Of Pregnant Women Care Services by Tuha Peut in Reducing Chronic Energy Lack (KEK) - Nurmalisa; Fitriani (Jurnal EduHealth, 2022)
Chronic Energy Deficiency (CED) in pregnant women has the potential to experience this which is often serious in society. There are many problems (CED) experienced in Blang Sepak Nagan Raya Village. So it requires service and attention to reduce CED problems. Tuha Peut members of Blang Sapek village participate in overcoming the problem of Chronic Energy Deficiency (CED) that pregnant women feel there is a solution in creating acceptance of care services for pregnant women. one of them is by controlling, participating in posyandu activities and so on. Data was collected through direct interviews with village midwives, pregnant women, Tuha Peut, and Blang Nagan Raya village cadres. The results of the interviews show that the efforts made by Tuha Peut in reducing CED by providing services for pregnant women, advising pregnant women to maintain their diet, providing vitamins, and maintaining nutritional intake for pregnant women and also providing PMT, FE tablets and milk can prevent anemia. . For this reason, the number of pregnant women in the village of Blang Sapek Nagan Raya is 0%.